Learning PowerPoint 2016 for Mac : a beginners guide to creating high quality presentations - Vaccaro, Guy (O'Reilly, 2015)
"This course is designed for the absolute beginner, meaning no previous experience with PowerPoint is required. You will start by learning how to create a new presentation, then jump into learning how to design slides. From there, this video will teach you about charts and graphs, organization charts, WordArt, shapes, SmartArt, and images. This video tutorial also covers how to manage and run the presentation, add animations, access master slides, and use templates. Finally, you will learn how to print your slides, and how to share your presentation online. Once you have completed this computer based training course, you will be fully capable of using PowerPoint for Mac to create your own presentations and run your own slideshows. Working files are included, allowing you to follow along with the author throughout the lessons."--Resource description page.